A Preliminary Study of the Effects of Gaseous Ozone on the Microbiological and Chemical Characteristics of Whole-Plant Corn Silage - Douglas Luiz Koakoski; Tiago Bordin; Damiano Cavallini; Giovanni Buonaiuto (Fermentation, 2024)
This study investigated the effect of gaseous ozone (O3) on the chemical and microbiological properties of whole-plant corn silage. Conducted on a commercial dairy farm in Brazil, maize was ensiled in experimental bag silos and treated with varying levels of O3 (0%, 1.25%, 3.12%, 4.15%, and 6.25%). The findings revealed minimal nutrient losses in starch, non-fiber carbohydrates, crude protein, and total digestible nutrients compared to untreated fresh maize. O3-treated silages exhibited increased levels of ash, ether extract, calcium, and phosphorus. Notably, the application of 3.12% to 4.15% O3 improved microbiological characteristics, significantly reducing mold and yeast populations, which are common issues in farm-produced silage. This study demonstrated that gaseous ozone is a promising additive for enhancing the microbiological quality of corn silage, offering an effective alternative to traditional chemical preservatives.